Is Public Sector More Attractive than Private Sector for Albanian Millennial Employees? - Mitllari, Eralda; Mimoza Kasimati (European Journal of Multidisciplinary Studies, 2018)
Millennials generation is very discussed today as they seem to be different from elder generations. They have been judged about the way they think, act, and expect things from others, but despite that, it is very important to know their characteristics and expectations, in order to get in with them in every relation. Millennials as employees are the challenge for every employer today, as they have to react according to millennials’ expectations, while managing the three current generations simultaneously in the workplace. This paper presents discussion of some of the most important activities that public sector in Albania is engaged to get in with millennials’ expectations and attract them. Internship programs, participation in work fairs, specific meetings with students, financing studies, trainings, use of social networks are some of the activities that public sector is mostly using to help on this, but are they attractive enough to Albanian millennials?